2013
DOI: 10.1093/hmg/ddt187
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of KIAA2022 causes mild to severe intellectual disability with an autism spectrum disorder and impairs neurite outgrowth

Abstract: Existence of a discrete new X-linked intellectual disability (XLID) syndrome due to KIAA2022 deficiency was questioned by disruption of KIAA2022 by an X-chromosome pericentric inversion in a XLID family we reported in 2004. Three additional families with likely pathogenic KIAA2022 mutations were discovered within the frame of systematic parallel sequencing of familial cases of XLID or in the context of routine array-CGH evaluation of sporadic intellectual deficiency (ID) cases. The c.186delC and c.3597dupA KIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 20 publications
6
77
1
1
Order By: Relevance
“…Height was typically two standard deviations below the mean and microcephaly was present in half. Mutations included an X-chromosome inversion with breakpoint in exon 1; a 70 kb microduplication containing exon 1; and two frameshift mutations (c.186delC and c.3597dupA) resulting in premature stop codons [Van Maldergem et al, 2013]. In the family with the X-chromosome inversion, one of the two obligate female carriers was evaluated and found to have a skewed X-inactivation pattern but remained asymptomatic [Cantagrel et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Height was typically two standard deviations below the mean and microcephaly was present in half. Mutations included an X-chromosome inversion with breakpoint in exon 1; a 70 kb microduplication containing exon 1; and two frameshift mutations (c.186delC and c.3597dupA) resulting in premature stop codons [Van Maldergem et al, 2013]. In the family with the X-chromosome inversion, one of the two obligate female carriers was evaluated and found to have a skewed X-inactivation pattern but remained asymptomatic [Cantagrel et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic spectrum includes moderate to severe ID with autistic features, poor or absent speech, epilepsy, and mild facial dysmorphisms [Van Maldergem et al, 2013]. Thus far, all reported males with KIAA2022 mutations are symptomatic while all reported females are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new genetic factors affecting neuritogenesis, growth cone changes, and vesicle and membrane trafficking have been identified as related to autism (Grice and Buxbaum 2006;Castermans et al 2010;Volders et al 2011;van Maldergem et al 2013). At least in a subgroup of patients, alterations in genes associated with neuronal vesicle trafficking (e.g., secretory carrier membrane protein 5-SCAMP5) coincide with the elaboration of mature synapses and may represent functional candidates for autism pathology (Castermans et al 2010).…”
Section: Alterations In Neuritogenesis In Autismmentioning
confidence: 99%
“…Furthermore, length and branching of neurites were found to be dependent on the neural cell adhesion molecules called contactins (Mercati et al 2013). Impairment in neurite outgrowth, including both dendrites and axons, was associated with mutation in the gene for the purinergic receptor and was manifested by intellectual disability within an autism spectrum disorder (van Maldergem et al 2013). Another study associated gene encoding enzyme monoamine oxidase B and proteins involved in regulation of neurite outgrowth with autism pathology (Piton et al 2011).…”
Section: Alterations In Neuritogenesis In Autismmentioning
confidence: 99%
“…KIAA2022 is also known as an X-linked mental retardation protein related to neurite extension (XPN), 31) and it plays a role in regulating cell-cell and cell-matrix adhesion and migration. 32) It has been shown that the dysregulated cell-cell and cell-matrix adhesion signaling pathways contribute to heart birth defects during heart organogenesis.…”
Section: Discussionmentioning
confidence: 99%